Real-Time Atmospheric Cloud Rendering System - Ford, Parker; Sung, Kelvin (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI), 2024)
High-quality cloud rendering is important when creating believable virtual outdoor environments. However, because of the complex physical processes involved in cloud formation and illumination, rendering realistic clouds in real-time is challenging. Research in the area has targeted limited-scope issues in relative isolation and presented impressive but focused results. For example, solutions for cloud modeling without details on rendering, or approximations of specific inter-scattering illumination without details on the rendering framework. These isolated solutions, combined with the required advanced system knowledge for efficient implementation, present a high barrier for holistic exploration and experimentation. This paper presents a real-time cloud rendering system that integrates an effective cloud modeling solution [1] with an efficient implementation [2] of a volumetric rendering framework [3] and incorporates recent findings in inter-droplet scattering [4] [5]. Additionally, a novel Temporal Anti-Aliasing solution is introduced to unify and support independent control over the sampling of both pixel areas and volumetric intervals. The resulting real-time cloud rendering system exemplifies recent advancements in the field and can serve as a convenient starting point for further investigations into cloud formation and illumination.